Cord blood procalcitonin and Interleukin-6 are highly sensitive and specific in the prediction of early-onset sepsis in preterm infants. (August 2014) - Steinberger, Eva; Hofer, Nora; Resch, Bernhard
Abstract We studied the predictive value of cord blood procalcitonin (PCT) and interleukin-6 (IL-6) in the diagnosis of early-onset sepsis (EOS) in the preterm infant. Retrospectively, PCT and IL-6 were correlated with clinical and/or blood culture positive EOS and negative infectious status between February 2008 and March 2011. Receiver operating curves (ROC) were generated and the area under the curve (AUC) was calculated by use of Youden's Index to detect the best cut-off values for sensitivity and specificity. Thirty of 218 preterm infants (13.8%) were diagnosed as having EOS. The optimal cut-off value for PCT was 0.235 μg/L (sensitivity 78.6%, specificity 86.3%), and for IL-6 15.85 ng/L (sensitivity 73.7%, specificity 84.2%), the combination of PCT and IL-6 revealed sensitivity 77.1% and specificity 91.7%. The combined determination of PCT and IL-6 from cord blood was highly sensitive and specific in the prediction of EOS.